2015
DOI: 10.1021/acs.nanolett.5b00124
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Crystal Facets in Gold Nanorods

Abstract: Metal nanocrystals can be grown in a variety of shapes through the modification of surface facet energies via surfactants. However, the surface facets are only a few atoms wide, making it extremely challenging to measure their geometries and energies. Here, we locate and count atoms in Au nanorods at successive time intervals using quantitative scanning transmission electron microscopy. This enables us to determine the atomic-level geometry and the relative stability of the facets and to expound their relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 31 publications
3
55
0
Order By: Relevance
“…In Figure c–e, 3D visualizations along different viewing directions and a slice through the reconstructed volume are presented. Although the reconstruction did not enable a direct indexing of the lateral facets due to surface roughness, the facets at the sides of the tip could be reliably investigated and were determined to correspond to {111} and {110} planes, in agreement with the findings reported by Katz‐Boon et al…”
Section: Structural and Morphological Characterizationsupporting
confidence: 83%
“…In Figure c–e, 3D visualizations along different viewing directions and a slice through the reconstructed volume are presented. Although the reconstruction did not enable a direct indexing of the lateral facets due to surface roughness, the facets at the sides of the tip could be reliably investigated and were determined to correspond to {111} and {110} planes, in agreement with the findings reported by Katz‐Boon et al…”
Section: Structural and Morphological Characterizationsupporting
confidence: 83%
“…[6] Reports on the crystalline structure of gold nanorod (AuNR) according to TEM data differ in their results. [2,[7][8][9][10][11][12][13][14] Wang et al reported an octagonal cross section with alternating (100)/(110) facets and tips covered with (110) and (111) facets. [12] Carbo-Argibay et al [10] suggested high-index surface facets such as (250) and (520).…”
Section: Doi: 101002/ppsc201900323mentioning
confidence: 99%
“…Reports on the crystalline structure of gold nanorod (AuNR) according to TEM data differ in their results . Wang et al reported an octagonal cross section with alternating (100)/(110) facets and tips covered with (110) and (111) facets .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…6) to nearly 100 %. [13] These recent studies point to the fact that the interaction with surfactants and ions can lead to ar eduction in the relative energy of ah igh-index facet. [11,12] An anorod geometry with eight identical high-index lateral Au(250) facets [11] is shown in Figure 1b.Ananorod that consists of octagonal Au(5120) side facets,terminating in pyramids with Au(130) facets at the two ends that are connected to the sides by four small Au(5120) "bridging" facets, [12] is reported in Figure 1c.Coexisting highand low-index facets,n amely an alternating sequence (1+ + ffiffi ffi 2 p ,1,0), (110), (1,1+ + ffiffi ffi 2 p ,0), (010), and so on, with comparable stability and dimensions have also been reported.…”
mentioning
confidence: 99%